Prenatal marijuana exposure and neonatal outcomes: a retrospective cohort study. Issue 9 (28th September 2022) - Jones, Michael James; Lotfi, Asma; Lin, Amber; Gievers, Ladawna L; Hendrickson, Robert; Sheridan, David C
Abstract : Objectives: Previous literature on the effects of marijuana exposure on neonatal outcomes has been limited by the reliance on maternal self-report. The objective of this study was to examine the relationship of prenatal marijuana exposure on neonatal outcomes in infants with marijuana exposure confirmed with meconium drug testing. Design: Retrospective cohort study. Setting and participants: Meconium drug screens obtained on infants born in a hospital system in the Pacific Northwest in the USA over a 2.5-year period. 1804 meconium drug screens were initially obtained, with 1540 drug screens included in the analysis. Primary and secondary outcome measures: Neonates with meconium drug screens positive for delta-9-tetrahydrocannabinol (THC) only were compared with neonates with negative drug screens. The following neonatal outcomes were examined: gestational age, preterm birth (<37 weeks), birth weight, low birth weight (defined as birth weight <2.5 kg), length, head circumference, Apgar scores and admission to the neonatal intensive care unit (NICU). Using multivariable logistical and linear regression, we controlled for confounding variables. Results: 1540 meconium drug screens were included in the analysis, with 483 positive for delta-9-THC only. Neonates exposed to delta-9-THC had significantly lower birth weight, head circumference and length (p<0.001). Neonates with THC exposure had 1.9 times the odds (95% CI 1.3 to 2.7, p=0.001) of being defined as low birth weight. Birth weight was on average 0.16 kg lower (95% CI 0.10 to 0.22, p<0.001) in those exposed to THC. Conclusions: Prenatal marijuana exposure was significantly associated with decreases in birth weight, length and head circumference, and an increased risk of being defined as low birth weight. These findings add to the previous literature demonstrating possible negative effects of prenatal marijuana use on neonatal outcomes.